Economic Backlash on the Cameroon Development Corporation (CDC) at the End of British Rule in Southern Cameroons, 1961-1968 - Takang, Bessong Stephen; Takor, Nixon Kahjum; Ngwa, Canute A. (International Journal of Scientific Research and Management (IJSRM), 2022)
The Cameroon Development Corporation (CDC) was created in 1946 and went operational in 1947 through the enactment of two important ordinances by the government of Nigeria. As an agro-industrial company, the principal objective at inception was the management of the ex-German plantations in Cameroon for the welfare of the workers in particular, and the inhabitants of Southern Cameroons in general. Curiously, the creation of the CDC coincided with a rising spirit of nationalism in the territory, culminating in the granting of independence by reunification with the Republic of Cameroon in October 1961. Considering that the end of British rule was accompanied by reunification, and not integration with Nigeria, the objective of this paper is to highlight the post reunification implications on the CDC. Even though it drastically reduced Nigerian domination of the plantations and offered the corporation greater access to seaport facilities in Douala, the article posits that the CDC suffered enormous setbacks at the end of the British trusteeship in the territory. Using qualitative historical designs, the finding of the study admit that the end of British rule provoked the suspension of Commonwealth funding, cancellation of banana trade preferences, tariff imbroglio, cross-territory security concerns, among the other constraints. However, the article concludes that the federal government equally embarked on a number of remedial measures which went a long way in mitigating the post-independence challenges faced by the CDC.KEY WORDS: Economic backlash, Cameroon Development Corporation, British rule and Southern Cameroons.